KOMUNITAS FITOPLANKTON KAITANNYA DENGAN KUALITAS PERAIRAN DANAU SENTANI - Sulawesty, Fachmijany (Research Center for Limnology, 2016)
Phytoplankton response to changes in the environment can be seen from changes in species diversity and abundance. Lake Sentani is one of the large lakes located in Papua Province, precisely in the district of Jayapura. Various activities in this lake will affect the waters quality of Lake Sentani, then made observations regarding the composition and abundance of phytoplankton in Lake Sentani. Observations were made in April 2014 at eight locations in the Lake Sentani are assumed to represent the condition of the waters of the lake. Samples taken as many as 10 liters of water, filtered using a plankton net no. 25, and preserved with Lugol 1%. Abundance computed using Sedgwick Rafter method. Analysis of the phytoplankton community structure seen by calculating the Diversity Index, Eveness Index and Dominance Index. There are six phyla and 50 species of phytoplankton were found, comprised of Chlorophyta (23 species), Cyanophyta (6 species), Bacillariophyta (18 species), Chrysophyta (1 species), dinoflagellate (1 species) and Euglenophyta (1 species). The abundance of phytoplankton in April 2014 ranged between 231-11.693 individual/Liter. Based on its abundance, the category of Lake Sentani mesotrofik, even when viewed from the dominant species, the tendency is eutrophic. Diversity Index ranged from 0.609 to 2.464 indicates low to moderate community stability, Eveness Index ranged from 0.047 to 0.243, this value is close to zero means the uniformity among species in community is lower, there is usually a species that dominates. If viewed from Dominance Index, dominance species occur in some areas of observation at Lake Sentani. CCA ordination showed no major effect of phosphate parameter on phytoplankton distribution in any location either on the surface and secchi depth. But in the bottom waters, phosphate, nitrate, dissolved oxygen, pH and temperature have an influence on the distribution of phytoplankton in Lake Sentani .